Modulating local structural disorder in layered cathodes with alternating edge- and face-sharing octahedra for enhanced high-rate performance - Chengjun Fan; Xiaoxia Yang; Lingling Yao; Qin Wang; Xiao Ouyang; Leidang Zhou; Zhiwen Gao; Rui Jia; Xibang Chen; Jing Chen; Hao Liu; Bin Liao; et al. (Chemical Engineering Journal, 2026)

Comparison of quality differences in Gastrodia elata wines fermented with different Saccharomyces cerevisiae and potential for sleep improvement in S. cerevisiae SY G. elata fermented wine - Zhiqiang Yi; Weizhong Hu; Huiying Li; Shuxin Zhou; Chengjun Jing; Quang D. Nguyen; Szilárd Kun; Szandra Klátyik; Zhirong Wang; Jianquan Kan; Muying Du (Food Bioscience, 2026)

Pediococcus acidilactici XZ106 ameliorates hyperglycemia in mice via steroid hormone and AMP-activated protein kinase pathway modulation - Shuxin Zhou; Weizhong Hu; Jianquan Kan; Zsolt Zalan; Chengjun Jing; Muying Du (Food Bioscience, 2026)

Hierarchical dual-crosslinked hydrogel electrolyte with quaternary ammonium and nanofiber reinforcement for durable and flexible zinc-ion batteries - Jiahui Li; Yaxin Wang; Chengxu Wang; Hao Wu; Sheng Li; Jing Ma; Jian Ni; Zhonglong Zhao; Xiaofang Jia; Fuhua Hou; Yanlai Wang; Chengjun Zhu; et al. (Chemical Engineering Journal, 2026)

Experimental and numerical investigation on deck system of a 102 m simply supported prestressed UHPC box-girder highway bridge - Sui Luo; Hua Zhao; Dongqin Qiao; Chengjun Tan; Xudong Shao; Jing Ma; Huangguo Qian; Zhilian Liao; Zhentao Hu; Cuizhu Zhou (Engineering Structures, 2024)

Concept and flexural performance of non-prestressed steel plate-UHPC-NC composite girder bridge - Lei Tu; Hua Zhao; Dongqin Qiao; Junde Hu; Chengjun Tan; Jing Ma; Zhentao Hu; Huiren Qiu; Xudong Shao (Engineering Structures, 2024)

Evaluation of characteristics on the indoor dwelling environments of traditional villages in Hehuang area of China based on basic environmental parameters under remote sensing technology - Hongbin Ma; Chengjun Jing; Ang Hu; Lihua Ma (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Positive effects of vegetation restoration on the soil properties of post-mining land - Cuihuan Li; Yongkang Ji; Nan Ma; Jing Zhang; Hui Zhang; Chengjun Ji; Jiangling Zhu; Junjiong Shao; Yan Li (Plant and Soil, 2024)

Wnt10a downregulation contributes to MEHP-induced disruption of self-renewal and differentiation balance and proliferation inhibition in GC-1 cells: Insights from multiple transcriptomic profiling - Yifan Hong; Xiazhu Zhou; Qi Li; Jing Chen; Yuexin Wei; Siyuan Wang; Xiangqin Zheng; Jie Zhao; Chengjun Yu; Jun Pei; Jie Zhang; Chunlan Long; et al. (Environmental Pollution, 2023)

Coupled anaerobic methane oxidation and metal reduction in soil under elevated CO 2 - Chenchao Xu; Naifang Zhang; Kaihang Zhang; Shuyao Li; Qing Xia; Jing Xiao; Maojun Liang; Weilei Lei; Junpan He; Gaiping Chen; Chengjun Ge; Xunhua Zheng; et al. (Global Change Biology, 2023)
Continued current emissions of carbon dioxide (CO 2 ) and methane (CH 4 ) by human activities will increase global atmospheric CO 2 and CH 4 concentrations and surface temperature significantly. Fields of paddy rice, the most important form of anthropogenic wetlands, account for about 9% of anthropogenic sources of CH 4 . Elevated atmospheric CO 2 may enhance CH 4 production in rice paddies, potentially reinforcing the increase in atmospheric CH 4 . However, what is not known is whether and how elevated CO 2 influences CH 4 consumption under anoxic soil conditions in rice paddies, as the net emission of CH 4 is a balance of methanogenesis and methanotrophy. In this study, we used a long‐term free‐air CO 2 enrichment experiment to examine the impact of elevated CO 2 on the transformation of CH 4 in a paddy rice agroecosystem. We demonstrate that elevated CO 2 substantially increased anaerobic oxidation of methane (AOM) coupled to manganese and/or iron oxides reduction in the calcareous paddy soil. We further show that elevated CO 2 may stimulate the growth and metabolism of Candidatus Methanoperedens nitroreducens , which is actively involved in catalyzing AOM when coupled to metal reduction, mainly through enhancing the availability of soil CH 4 . These findings suggest that a thorough evaluation of climate‐carbon cycle feedbacks may need to consider the coupling of methane and metal cycles in natural and agricultural wetlands under future climate change scenarios.

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Levels of urinary metabolites of benzene compounds, trichloroethylene, and polycyclic aromatic hydrocarbons and their correlations with socioeconomic, demographic, dietary factors among pregnant women in six cities of China - Jing Zhu; Xuan Zhao; Mi Yang; Bo Zheng; Chengjun Sun; Xiaoli Zou; Zhen Liu; Kouji H. Harada (Environmental Science and Pollution Research, 2022)

Complete genome sequence of a novel mitovirus from the phytopathogenic fungus Fusarium oxysporum - Jing Wang; Chengjun Li; Rui Qiu; Xiaojie Li; Jun Zhao; Jingke Bai; Yuguo Chen; Shujun Li (Archives of Virology, 2021)